Corneal curvature and thickness development in premature infants. - De Silva, Silvana; Parentin, Fulvio; Michieletto, Paola; Pensiero, Stefano (J Pediatr Ophthalmol Strabismus, 2011)
PURPOSE: Analysis of postnatal changes in central corneal thickness (CCT) and corneal curvature (CC) in premature infants, their relation, and their possible influence on eye growth and intraocular pressure (IOP) evaluation. METHODS: CCT and CC were assessed in both eyes of 56 premature infants, born at 24 to 32 weeks of gestational age (GA), and then two or three times at post-conceptional ages (PCAs) of 28 to 42 weeks. RESULTS: CC changed from 65.83 diopters at 28 weeks of PCA to 49.38 diopters at 42 weeks of PCA. CCT decreased from 794 to 559 μm at the same ages. The reductions of these two corneal parameters seem to be related to each other and begin immediately after birth. CONCLUSION: In light of the few data available in the literature, these data provide more certainty about the CCT values of premature infants. The importance of CCT and CC fast variations after premature birth concerns both the knowledge of anterior segment development and the correct evaluation of IOP in immature eyes; the influence of these two parameters on the methods of IOP evaluation could be more remarkable at the lowest PCAs.
Keywords: Child Development; Cornea; Corneal Pachymetry; Eye; Female; Gestational Age; Humans; Infant, Newborn; Infant, Premature; Intraocular Pressure; Male; Premature Birth